The latest progress on miR‐374 and its functional implications in physiological and pathological processes. Issue 5 (17th February 2019) - Bian, Hongjun; Zhou, Yi; Zhou, Dawei; Zhang, Yongsheng; Shang, Deya; Qi, Jianni
Abstract: Non‐coding RNAs (ncRNAs) have been emerging players in cell development, differentiation, proliferation and apoptosis. Based on their differences in length and structure, they are subdivided into several categories including long non‐coding RNAs (lncRNAs >200nt), stable non‐coding RNAs (60‐300nt), microRNAs (miRs or miRNAs, 18‐24nt), circular RNAs, piwi‐interacting RNAs (26‐31nt) and small interfering RNAs (about 21nt). Therein, miRNAs not only directly regulate gene expression through pairing of nucleotide bases between the miRNA sequence and a specific mRNA that leads to the translational repression or degradation of the target mRNA, but also indirectly affect the function of downstream genes through interactions with lncRNAs and circRNAs. The latest studies have highlighted their importance in physiological and pathological processes. MiR‐374 family member are located at the X‐chromosome inactivation center. In recent years, numerous researches have uncovered that miR‐374 family members play an indispensable regulatory role, such as in reproductive disorders, cell growth and differentiation, calcium handling in the kidney, various cancers and epilepsy. In this review, we mainly focus on the role of miR‐374 family members in multiple physiological and pathological processes. More specifically, we also summarize their promising potential as novel prognostic biomarkers and therapeutic targets from bench to bedside.